Political Dynasties Undermine Democratic Governance and Constitutional Integrity in Indonesia: Dinasti Politik Melemahkan Tata Kelola Demokratis dan Integritas Konstitusional di Indonesia - Aulia Putri Insani; Aldlyan Meilani; Nurul Iman (Academia Open, 2026)
Political dynasties represent a systemic challenge to Indonesia’s constitutional democracy by consolidating hereditary power that contradicts the principles of meritocracy, equal political access, and institutional accountability. This research aims to analyze how political dynasties distort democratic governance and weaken constitutional mechanisms that safeguard state integrity. Using a library research method supported by systematic content analysis of academic literature, legal sources, and policy documents, the study finds that dynastic politics institutionalize oligarchic power structures, suppress competitive leadership regeneration, and increase risks of corruption, collusion, and nepotism. The findings demonstrate that dynastic networks interfere with the separation of powers, politicize public resource allocation, bias representative functions toward familial interests, and reduce institutional autonomy within the constitutional framework. Although dynasties may provide policy continuity in certain contexts, these advantages are conditional and outweighed by structural threats to legal integrity and public trust. The novelty of this study lies in extending the discussion from electoral and regional governance to the broader constitutional domain, characterizing dynastic politics as a constitutional disruption rather than merely a political phenomenon. The implications suggest the need for transparent political recruitment, regulatory restrictions on hereditary candidacy, enhanced oversight mechanisms, and civic education to reinforce democratic resilience. These measures are essential to prevent the normalization of hereditary power and to protect constitutional democracy in Indonesia from long-term institutional degradation. Highlights • Political dynasties weaken constitutional accountability and democratic governance• Hereditary power restricts leadership succession and public institutional autonomy• Oligarchic networks increase corruption risks and distort public representation Keywords Political Dynasties; Constitutional Democracy; Democratic Governance; Meritocracy; Oligarchic Power